Dual-Band Wearable Fluidic Antenna With Metasurface Embedded In A PDMS Substrate - Muhammad Nazrin, Ramli; Ping, Jack Soh; Mohd Faizal, Jamlos; Herwansyah, Lago; Norazizan, Mohd Aziz; Azremi, Abdullah Al-Hadi (Springer, 2017)
A flexible fluidic antenna with an artificial magnetic conductor (AMC) plane is presented in this work. The overall structure is embedded in polydimethylsiloxane (PDMS), while the radiator is fabricated using eutectic gallium indium alloy (EGaIn) conductor. This radiator operating over an AMC plane is designed based on a rectangular patch which is integrated with slot and slits to enable dual-band WLAN ISM (2.4 and 5.8 GHz) operation, while maintaining a compact form. The integration of the AMC plane behind the proposed antenna reduced backward radiation towards the human users and improved gains. The evaluation of the antenna integrated with the AMC plane indicated satisfactory performance in terms of reflection coefficient, bandwidth and radiation patterns.